Determining the change in length of the anterolateral ligament during knee motion: A three-dimensional optoelectronic analysis. (February 2019) - Neri, Thomas; Testa, Rodolphe; Laurendon, Loic; Dehon, Margaux; Putnis, Sven; Grasso, Samuel; Parker, David A.; Farizon, Frederic; Philippot, Remi
Abstract: Background: The variation of the anterolateral ligament (ALL) length during knee motion is still unclear, and the knee position in which a reconstruction graft should be tensioned remains controversial. The objective of this study was to determine the variation of the ALL length during knee motion using a three-dimensional optoelectronic system. Methods: Kinematic analyses of 20 cadaveric knees were performed using a Motion Analysis® system. The variability of the measurements made during the five acquisition cycles was studied. Reliability was evaluated by two separate measurement sessions, with complete system reinstallation, using different cadavers and a new operator. The ALL length was analysed from extension to full flexion in three rotational conditions. Findings: When analysing the reliability of the five cycles, 82% of the measurements we found to have an Intra Class Correlation (ICC) >0.85. The reproducibility of inter-sessional measures by different operators and different cadavers was either good (ICC >0.75) or excellent (ICC >0.85). The ALL length was maximum in full internal rotation with the knee at 25° of flexion. Interpretation: This three-dimensional optoelectronic protocol allowed us to analyse the variation of the ALL length during intact knee motion with good reliability and the required accuracy to analyse this variable. The maximal length and highest tension of the ALL was reported at 25° of knee flexion in internal rotation, suggesting this as the optimal position for the knee joint when tensioning an ALL reconstruction. Highlights: Knee motion can be accurately assessed using 3D optoelectronic motion capture. The protocol established is reliable, allowing accurate ALL length analysis. The ALL length is maximum in full internal rotation with the knee in 25° of flexion.